The Influence of Social Media Activities on Brand Loyalty: The Mediating Role of Brand Equity with the S-O-R Model on Netflix Customers - Febby Gracea Ekklesi; Oliandes Sondakh (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
In recent years, the internet has become increasingly popular in Indonesia, transforming individual behavior and creating new habits that were impossible with traditional media. The rise of the internet has also revolutionized global communication and entertainment, particularly through social media and SVOD platforms like Netflix, which has now become the world's most popular entertainment application. This study aims to analyze the influence of Entertainment, Interactivity, Trendiness, Customization, and EWOM on Brand Equity, as well as the role of Brand Equity in shaping Brand Loyalty among Netflix customers in East Java. The findings are expected to contribute to marketing theory development and assist Netflix in evaluating the impact of these variables on Brand Equity and Brand Loyalty.This study employs a quantitative method with data processing conducted through Smart PLS®4. Data were collected from 188 respondents aged 18-58 years, who are Netflix users residing in East Java and following Netflix's Instagram account. The results indicate that Brand Equity has the most significant impact on Brand Loyalty (0.614), followed by Trendiness on Brand Equity (0.434), EWOM on Brand Equity (0.203), and Customization on Brand Equity (0.185). Meanwhile, Entertainment and Interactivity have almost no influence on Brand Equity, with values of 0.001 and 0.000, respectively.This study contributes to theory, practice, and strategic aspects of social media marketing. Theoretically, it enriches the literature on brand equity and brand loyalty through elements such as entertainment, interactivity, and EWOM. Practically, the findings help Netflix develop a more personalized and interactive digital marketing strategy. From a strategic perspective, this study supports the optimization of big data and engagement marketing campaigns to enhance customer engagement and strengthen brand equity